The Shiroroga Pratikara Prakarana of Chikitsanjan: An Annotated Review - Vasava, Ashvinee N; Vyas, Hitesh A; Baghel, Arjun Singh; Singh, Preetpal; Vasani, Dharmik (International Research Journal of Ayurveda & Yoga, 2025)
Background: Chikitsanjan is a concise textbook of formulations that covers accessible medicines and comfortable treatments, written by Upadhyaya Vidyapati probably in the 17th century. This text has been published only twice. In this effort, the second and currently available publication has been considered for review, which contains 267 verses. This text describes the treatment of a total of 42 diseases. Where the maximum number of verses are in Jvara Prakarana (fever), Striroga Prakarana (gynecological disorders), and Shiroroga Prakarana (diseases of the head). Materials and Methods: Shiroroga Pratikara Prakarana from Chikitsanjan published by Sastusahitya Prakashana, Ahmedabad, Gujarat, in the year 1979 has been used for detailed review. Shiroroga Pratikar Prakarana has been selected due to the high prevalence of diseases in the present era, the maximum number of verses, and the unique concept of treatment. Observation and Results: Treatment of Shiroroga has been described in 13 verses which contain mainly external applications in the form of Lepa (11 out of 13). Only one Nasya (formulation for nasal administration) is described. One unique treatment with Yantra (a geometrical diagram used in Hindu rituals) is also used. Conclusion: The Shiroroga Pratikara Prakarana of Chikitsanjan outlines the treatment of eight types of diseases of the head, scalp, and hair using Lepa, Nasya, and Yantra. Furthermore, the treatment of diseases by the invisible power of the Yantra can develop and complement the Daivavyapashraya Chikitsa (Spiritual therapy) of Ayurveda.